2017
DOI: 10.1159/000485877
|View full text |Cite
|
Sign up to set email alerts
|

The MiR-495/Annexin A3/P53 Axis Inhibits the Invasion and EMT of Colorectal Cancer Cells

Abstract: Background/Aims: More and more reports have shown that the dysregulation of miRNAs can contribute to the progression and metastasis of human cancers. Many studies have shown that the down-regulation of the miR-495 level occurs in a variety of cancers, including colorectal cancer (CRC). However, the precise molecular mechanisms of miR-495 in CRC have not been well clarified. In the current study, we investigated the biological functions and molecular mechanisms of miR-495 in CRC cell lines. Methods: qRT-PCR was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The EMT, in which epithelial cells lose polarity and gain the stromal phenotype, has been invoked as a critical component of the metastatic process [35- 38]. Different studies have shown that the suppression of E-cadherin is a vital molecular event involving specific E-boxes located in the proximal elements of promoters [24, 39]. The pattern of E-cadherin loss is currently thought to be transcriptional repression of CDH1 in different malignancies [22].…”
Section: Discussionmentioning
confidence: 99%
“…The EMT, in which epithelial cells lose polarity and gain the stromal phenotype, has been invoked as a critical component of the metastatic process [35- 38]. Different studies have shown that the suppression of E-cadherin is a vital molecular event involving specific E-boxes located in the proximal elements of promoters [24, 39]. The pattern of E-cadherin loss is currently thought to be transcriptional repression of CDH1 in different malignancies [22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study provides new information on the roles of these miRNAs in CRC progression. Other miRNAs, such as miR-495, are known to influence CRC cell proliferation, invasion, migration and EMT [65,66]. MiR-495 was also found to directly affect the expression of invasion-related molecules, including MMP2 [65].…”
Section: Discussionmentioning
confidence: 99%
“…In esophageal squamous cell carcinoma, the expression levels of miR-495 were reported to be reduced in tumor tissues and significantly associated with lymph node metastasis, invasion and tumor, node and metastasis (TNM) stage (22). miR-495 was observed to be expressed at low levels in glioma (23,24), osteosarcoma (25), colorectal (35,36), gastric (37-39), prostate (40) and endometrial cancers (41), and renal cell carcinoma (42). miR-495 has been reported to be highly expressed in bladder (43) and breast (44) cancers; miR-495 upregulation in bladder cancer has been strongly correlated with larger tumor sizes, advanced TNM stages and lymph node metastasis (43).…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that restoration of miR-495 expression attenuated cell proliferation and invasion, and promoted the apoptosis of osteosarcoma cells (25). Ectopic expression of miR-495 was demonstrated to prohibit proliferation, colony formation, metastasis and epithelial-mesenchymal transition (EMT), and induce the apoptosis of colorectal cancer cells (35,36). Numerous studies have also demonstrated that miR-495 acts as a tumor suppressor in gastric cancer by regulating cell growth, motility and chemotherapy resistance (37-39,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation